Clinical considerations and challenges in TAV-in-TAV procedures - Hayek, Ahmad; Prieur, Cyril; Dürrleman, Nicolas; Chatelain, Quentin; Ibrahim, Reda; Asgar, Anita; Modine, Thomas; Ben Ali, Walid (Frontiers in Cardiovascular Medicine, 2024)
Transcatheter aortic valve replacement (TAVR) has emerged as a viable treatment for aortic valve disease, including low-risk patients. However, as TAVR usage increases, concerns about long-term durability and the potential for addition interventions have arisen. Transcatheter aortic valve (TAV)-in-TAV procedures have shown promise in selected patients in numerous registries, offering a less morbid alternative to TAVR explantation. In this review, the authors aimed to comprehensively review the experience surrounding TAV-in-TAV, summarize available data, discuss pre-procedural planning, highlight associated challenges, emphasize the importance of coronary obstruction assessment and provide insights into the future of this technique.